"Lost Cause" Memories and Cultural Amnesias: Mayor Mitch Landrieu's Tragicomic Speech on Confederate Monument Removals. (13th April 2021) - Carr, M. Kelly
Abstract : Objective: This essay examines the rhetorical strategies used in former New Orleans Mayor Mitch Landrieu's speech explaining the city's decision to remove several Confederate memorials. Method: The author performs a Burkean rhetorical analysis to the transcript and social context of Landrieu's May 19, 2017, speech. Additionally, the author applies frameworks of visual rhetoric, public memory, and third persona to engage Landrieu's construction of the memorials' meaning and their amnesias. Results: Landrieu used identification, a nuanced commemorative rhetorical analysis, and a comic frame to explain both the lure and the damaging falsehood of the Lost Cause narrative that the memorials represent. He reserved the tragic frame for those who continue to support the Lost Cause narrative. Conclusions: In this rhetorical move, Landrieu divides monument supporters between those explicitly tied to the Confederate cause of white supremacy—these people are consciously evil—and those who have been hoodwinked by the monuments' narrative—for these people, he offers redemption. The tragicomic frame made Landrieu's speech well received nationally and revealed promise through its distinction between supporters of white supremacy and passive adopters of the memorials' narratives. However, it did not appear to persuade monument supporters, revealing the limitations of an agency‐centered approach to combating the Lost Cause narrative.